Pulmonary blood flow, its reserve, and distribution in highly trained endurance athletes and healthy control subjects - Savolainen, A. M.; Han, C.; Kemppainen, J.; Oikonen, V.; Knuuti, J.; Kalliokoski, K. K.; Heinonen, I. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Pulmonary blood flow is an important factor in endurance sports performance, but studies investigating possible differences between athletes and matched healthy subjects are scarce. In the present study we measured pulmonary blood flow, its reserve and distribution in highly trained male endurance athletes (n=10, age=25±4 years, mostly cross-country skiers whose bicycle VO2max was 62±5 ml/kg/min) and untrained but fit healthy controls (n=10, age=26±4 years, VO2max=46±3 ml/kg/min) with [15O]water positron emission tomography (1-2) at rest and during adenosine infusion (140 mg/kg/min I.V.), a protocol commonly used in cardiac flow reserve studies. The athletes had been training on a regular basis for 12±4 years, 8.7±1.4 times and 12.8±1.5 hours a week primarily in endurance type of exercise at various intensities. They had started sport training at the age of 12.5±2.4, and competed in endurance sports for 15.6±4.5 years at high national and international level. The control men, on the other hand, had been performing physical activity only occasionally, less than three times per week. Our results indicate that pulmonary blood flow at rest and during adenosine stimulation was similar in both groups (in athletes, 213±55 ml/100ml/min in rest and 563±138 ml/100ml/min during adenosine infusion and in controls, 206±83 ml/100ml/ min and 473±212 ml/100ml/min, respectively, p=NS). Although the absolute pulmonary blood flow reserve was unchanged in athletes, blood flow heterogeneity was reduced from rest to adenosine infusion (from 84±18 % to 70±19 %, p<0.01) while remaining unchanged in healthy controls (77±16 % to 85±33 %, respectively, p=NS). Moreover, there was a marked gravitational influence of supine body posture on general pulmonary blood flow distribution so that clear dorsal dominance was observed both at rest (in athletes, 284±64 ml/100ml/ min dorsally vs.102±48 ml/100ml/min ventrally, p<0.001, and in controls, 290±115 ml/100ml/min vs.102±59 ml/100ml/min respectively, p<0.001) and during adenosine infusion (in athletes, 677±134 ml/100ml/min vs. 375±165 ml/100ml/min, p<0.001, and in controls, 642±179 ml/100ml/min vs. 320±200 ml/100ml/min, p<0.01), thus, training status did not have effect on flow distribution. Blood flow heterogeneity values were also markedly lower in the high perfusion dorsal areas at rest (in athletes, 63±17 % vs. 86±24 %, p<0.05, and in controls 53±18 % vs. 81±21 %, p<0.01) and during adenosine infusion (in athletes, 52±18 % vs. 97±22 %, p<0.001 and in controls 54±22 % vs.110±38 %, p<0.001). In conclusion, although highly trained endurance athletes appear not to have supranormal absolute pulmonary blood flow during adenosine stimulation, reduced blood flow heterogeneity may be an indication of capillary reserve which is more extensively recruitable in athletes than in matched healthy control subjects.